Analisis Kemampuan Hasil Berpikir Kritis terhadap Kemandirian Belajar pada Mata Pelajaran Matematika di SDN 2 Kertawinangun - Citra Patricia; Aulia Maharani (GENFABET: Generasi Pendidikan Dasar, 2024)
The purpose of this study was to determine the analysis of the ability to think critically on learning independence in mathematics at SDN 2 Kertawinangun Cirebon. The subjects of this study were fourth grade students consisting of 18 students who were selected in 2023. The sample in this study was collected using a convenience sampling technique. Data on critical thinking and independent learning in the form of questionnaires and options. This study uses several explanatory description data tests, descriptive statistical tests and Wilcoxon data tests. It is found that in the difference between the results of the independent learning test and students' critical thinking it can be seen that is the difference in each test score, there are 18 students as respondents. Based on the data from this test, there was a decrease from 18 respondents, a decrease in the mean rank and the sum of ranks. And it can be concluded that from students' critical thinking towards independent learning. This is because students are not used to using their minds in critical thinking in their independent learning so that data is not implemented optimally. Therefore, critical thinking is important in terms of improving students' abilities.